Structure of phytoplankton for the coastal waters in the eastern Aniva Bay of the Okhotsk Sea in 2018 - I. V. Motylkova; N. V. Konovalova (Известия ТИНРО)
Species composition, distribution density and biomass of phytoplankton were surveyed in the coastal area of eastern Aniva Bay in May-October 2018. In total, 297 species and intraspecific taxa of microalgae belonged to Bacillariophyta, Chlorophyta, Cryptophyta, Dinophyta, Euglenophyta, Crysophyta were found. Their total abundance ranged from 14.8 . 103 to 1024.7 . 103 cells/L, biomass was 19.4–324.6 mg/m3. Two peaks in the abundance (in June and October) and five peaks in the biomass (in May, June, September and October) were noted. The bulk of population was formed by diatoms in spring and autumn, and flagellates in summer. A bloom of potentially toxic diatoms of genus Pseudo-nitzschia was registered. In this connection, monitoring of toxic species is necessary for planning and development of aquaculture farms.